Global Value Chains Linking Local Producers from Developing Countries to International Markets - Trienekens, Jacques; van Dijk, Meine Pieter (EADI, 2011)
This important volume presents seven case studies of global value chains alongside two theoretical chapters concerning these chains. The contributors explore a wide range of issues relevant to value chains: the impact of global value chains on local upgrading strategies, the role of governance structures shaping global value chains, the role of buyers in creating, monitoring and enforcing commodity specifications and of international standards in shaping the patterns of chain governance. They also consider the role of donors, governmental organisations, and civil society in influencing value chains and the importance of partnerships as mechanisms for value chain upgrading. This carefully researched work is essential reading to scholars and students of the rapidly changing global economic order.